Apolipoprotein D Concentration in Human Plasma during Aging and in Parkinson's Disease: A Cross-Sectional Study. (26th March 2018) - Waldner, Andreas; Dassati, Sarah; Redl, Bernhard; Smania, Nicola; Gandolfi, Marialuisa
Abstract : Apolipoprotein D (ApoD), a lipocalin transporter of small hydrophobic molecules, plays an important role in several neurodegenerative diseases. ApoD is expressed in and secreted from a variety of peripheral and brain tissues. Increments of ApoD have been reported in relation with oxidative stress conditions, aging, and degeneration in the nervous system. Preliminary findings support the role of ApoD in neuroprotection. However, its role in PD remains unclear. To date, no studies have been performed on the relationship between ApoD in the blood and PD, as neurodegenerative pathology related to oxidative damage. We investigated the concentration of ApoD in the blood of healthy control subjects and PD patients with mild-to-moderate neurological impairment. ApoD plasma levels were measured using sandwich enzyme-linked immunosorbent assays (ELISA) in 90 healthy subjects (aging-analysis cohort) and in 66 PD patients at different stages compared with 19 age-matched healthy subjects. Significant age-related increase of ApoD was detected in subjects older than 65 years of age (p < 0.002 ). In PD patients, a significant increase in ApoD plasma concentration was found compared with healthy subjects of the same age (p < 0.05 ). ApoD and PD stage are significantly correlated (p < 0.05 ). ApoD might be a valid marker for the progression of PD.